ANALISIS PERUBAHAN PERATURAN DALAM MELAKUKAN INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA - Dwinanda, Irfan Alfieansyah (Faculty of Law, Universitas Pasundan, 2024)
The capital market plays a significant role in a country's economy, as it enables the functioning of economic and financial activities. Indonesia ranks first among ASEAN countries in terms of market capitalization, and the Financial Services Authority and the Indonesia Stock Exchange predict that the Indonesian stock market's capitalization still has the potential to grow even larger. The opportunity for significant capitalization encourages the government to facilitate IPO requirements, especially for start-ups and medium-sized enterprises. However, easing IPO requirements may have both positive and negative impacts on investors, securities, and issuers (company). This study is a normative juridical research using secondary data, which is then analyzed qualitatively. The research findings indicate that the number of companies conducting IPOs does not necessarily reflect the quality of the stock exchange. By granting permission to companies that have not yet recorded profits for IPOs, investors are encouraged to speculate on the movement of stock prices and the condition of the market. Therefore, it is necessary to formulate regulations regarding IPOs that still prioritize the principle of full disclosure.